Construction Standardization of Metal as a Technology Transfer Process in Social Interest Housing Programs - Soria H., Marco (2020)
Having as main objective Achieve the constructive standardization of metal as a process of technological transfer for the development of housing programs of social interest. This concern arises from the projective experience of long years of career in which the desire to achieve a more social, emotional and experiential architecture and above all that preserving its levels of spatial quality, functional efficiency, safety and excellent finishes, could always be redeemed. Be more accessible to the middle classes stationed in sectors C and D, and what better experience these alternatives in the thriving and progressive city of Huancayo. With a quantitative research approach, the research instruments used are; Observation cards bibliographic records and surveys, taking a sample of 80 families. The work had the following results: new project approaches from building with steel, the design of an efficient and functional collective housing; new resources to solve the housing need in the short term, reduced costs of execution and more efficient control of the processes and in some way increase the quality of housing life